ANALISIS KETERAMPILAN KOLABORASI SISWA SEKOLAH DASAR DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS GAMES EDUCAPLAY PADA PEMBELAJARAN IPAS - Abdullah Najib; Badruli Martati; Meirza Nanda Faradita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze students' collaboration skills in science learning using educaplay games-based learning media. The research method used in this research is qualitative. This research was conducted from January to. July 2024. The data collection techniques used were interviews, observation and documentation. For research analysis techniques using the Miles and Huberman Model. This research took place at SD Muhammadiyah 15 Surabaya, with research subjects being 5 grade 5 students. The research results based on observations, interviews and media obtained showed that in terms of indicators, 1) Active contribution, students are active in the discussion process or work on assignments, 2) Work productive, shows that students can share tasks well with each other, 3) Responsibility, shows that students can complete the tasks given on time, 4) Flexibility and compromise, shows that students collaborate with each other among group members, 5) Mutual respect, shows that students can unite opinions with other members. The conclusion of this research is that the use of educaplay games-based learning media in 5th grade science and science learning at SD Muhammadiyah 15 Surabaya shows that students discuss each problem solving, accept different opinions well, and are able to take responsibility for the questions that have been given. Keywords: educaplay, collaboration, IPAS